Septo-Optic Dysplasia in a Newborn Presenting with Bilateral Dilated and Fixed Pupils - Mehnaz Jabeen; Amber Hairfield; Leonard E. Swischuk; Sunil K. Jain (Thieme Medical Publishers, Inc., 2016)
Abstract Introduction We describe a newborn female infant with septo-optic dysplasia (SOD) presenting with bilateral dilated and fixed pupils. Conclusion Our report is unique because the incidental finding of bilateral dilated and fixed pupils on the newborn exam was the only clinical finding which led to a prompt work-up and eventual diagnosis of SOD.